Community-based management of hypertension in Nepal (COBMIN) - Khanal, Arjun (Kansas State University, 2017)
In COBMIN project, we explore two popular software architectural pattern to implement WHO (World Health Organization) STEPS Instrument for Non-Communication Diseases Risk Factor Surveillance for Nepal. COBMIN web application implements Model-View-Controller(MVC) pattern, which divides the application into three interconnected parts - model, view, and controller. Similarly, COBMIN mobile application utilizes one of the most popular Model-View-ViewModel (MVVM) software architectural pattern which isolates the development of graphical user interface from the business logic and data models. We implement above-mentioned pattern using new .Net Core technologies and a cross-platform mobile development API Xamarin.Forms. The COBMIN project comprises of a web application, a web API, and a mobile application to facilitate community-based management of hypertension in Nepal. The primary purpose of the web application is to manage demographic, behavioral, and physical information of the members of the community who are part of the study group. The mobile application is used to expedite the process of data acquisition from the members. The Web API defines request-response message system for mobile client application employing the central data storage.
Keywords: RESTMVC; MVVM; Xamarin; API